2013
DOI: 10.1016/j.cmet.2012.12.003
|View full text |Cite|
|
Sign up to set email alerts
|

Reproduction, Fat Metabolism, and Life Span: What Is the Connection?

Abstract: Reduced reproduction is associated with increased fat storage and prolonged lifespan in multiple organisms, but the underlying regulatory mechanisms remain poorly understood. Recent studies in several species provide evidence that reproduction, fat metabolism, and longevity are directly coupled. For instance, germline removal in the nematode Caenorhabditis elegans promotes longevity in part by modulating lipid metabolism through effects on fatty acid desaturation, lipolysis, and autophagy. Here, we review thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
213
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 272 publications
(225 citation statements)
references
References 107 publications
(183 reference statements)
10
213
0
2
Order By: Relevance
“…As many studies have indicated the increased fattening of insects in response to other stress‐induced conditions (Hansen et al., 2013; Moghadam et al., 2015; Piiroinen et al., 2014), we suggest that the increased body fat content in dung beetles from logged forests reinforces the use of this trait as a likely early warning biomarker to assess the environmental quality of disturbed tropical forests.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As many studies have indicated the increased fattening of insects in response to other stress‐induced conditions (Hansen et al., 2013; Moghadam et al., 2015; Piiroinen et al., 2014), we suggest that the increased body fat content in dung beetles from logged forests reinforces the use of this trait as a likely early warning biomarker to assess the environmental quality of disturbed tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction is a high cost process (Hansen et al., 2013), and fat content is considered the currency (Barry & Wilder, 2013). Although not always observed (Flatt et al., 2008; Wilder, Raubenheimer, & Simpson, 2015), the link between reduced reproduction and increased fat storage has been demonstrated for many insects (Hansen et al., 2013; Moghadam et al., 2015; Wilder et al., 2015). Similarly, previous research has found a positive relationship between reduced fecundity, increased fattening, and higher starvation stress resistance (Broughton et al., 2005; Hansen et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Recently, research in the nematode Caenorhabditis elegans has revealed novel insights into the relationship between metabolic status, reproduction and aging. [2][3][4] In worms, as in many other organisms, mating has damaging consequences for the female, including reducing its size, stress-resistance and lifespan. 5,6 Alternatively, removing the germline increases worm lifespan significantly, 7 in accordance with the observation that reduced fertility is often associated with increased lifespan in many species.…”
Section: Introductionmentioning
confidence: 99%